Autologous platelet-rich plasma (APRP) in diabetes foot disease: a meta-analysis - Ruiz-Muñoz, María; Martínez-Barrios, Francisco-Javier; Fernández Torres, Raúl; Lópezosa-Reca, Eva; Marchena-Rodríguez, Ana José (Elsevier, 2024)
Introduction This study will explore the effectiveness of autologous platelet-rich plasma in the treatment of diabetic foot disease compared to conventional treatments, based on the ulcer healing rate. Methods The electronic databases of PubMed, EMBASE, and WOS internet were searched. Evaluated outcome rate of complete ulcer healing. Statistical analysis was performed with RevMan 5.0 software and SPSS 25.0. Results Eleven RCTs with 828 patients were included in this study. The meta-analysis showed a higher complete ulcer healing rate (OR = 3.69, 95 % CI 2.62 to 5.20, P < 0.01, I2 = 0 %) in growth factors based in autologous platelech-rich plasma (aPRP) group compared with control. Mixed evidence was seen for publication bias, but analyses by using the trim-and-fill method did not appreciably alter results. Conclusion Autologous platelet-rich plasma can improve the complete healing rate of the ulcer compared to current conventional treatments in diabetic foot ulcer patients.
Keywords: Enfermería; Neuropatías diabéticas - Tratamiento; Autologous growth factors; Diabetic foot disease; Meta-analysis; Ulcer treatment; Randomised controlled trials; Platelet-rich plasma